Desenvolvimento de sistema microfluídico à base de silicone silpuran® para seleção de espermatozoides bovinos - Fernandes, Beatriz Dantas (Universidade Federal Rural do Semi-Árido, 2019)
Sperm selection consists of a fundamental stage in reproductive techniques such as PIVE. However, the methods usually used can cause damage to cell integrity. Microfluidic devices were developed in order to select sperm without the use of centrifugation and with time reduction. However, although these are made with materials considered low cost, they are still relatively expensive. The objective of this study was to evaluate the toxicity of a new microfluidic device made from Silpuran® silicone and to perform the selection of episdidymis sperm by testing chemotaxis by different substances. For this purpose, 10 epididymis testicle complexes were used for each part of the experiment and the kinetic parameters of sperm with the use of the computerized analysis system (CASA), morphology, integrity and viability of the plasma membrane. In experiment 1, to evaluate silicone toxicity, the slow thermoresistance test was used, in which the control and treatment samples were kept in incubator at 37.5ºC and evaluated at different times (0, 60, 120 and 180 min). The data were compared using the Mann-Whitey test. The parameters of MT, MP, VSL, VCL and VAP of the epididymis sperm deposited in the device were higher than those of the control. The use of Silpuran® silicone in the manufacture of microfluidic devices was not toxic to cells and presented satisfactory results in relation to the control. For experiment 2, referring to the saline selection, the microfluidic device, formed by a central reservoir and 4 more reservoirs around interconnected by canalics, was prepared with saline solution 0.9%, middle MIV, middle + matured oocytes and middle MIV + medroxiprogesterone acetate at 0.05% in peripheral reservoirs and a sample rate in the central reservoir. After filling, the device was incubated for 30 min. As a control technique, the Percoll® gradient was used. The data were compared using the Kruskall-Wallis test. The epididymis sperm collected from reservoirs containing SS, middle MIV and middle MIV + O were similar to that found by Percoll® technique. For the parameters of MT and MP, the MIV and MIV + O showed a higher percentage of morphologically normal sperm in relation to Percoll®. The microfluidic device was efficient in the selection of epididymis sperm, which were more attracted to the SS, MIV and MIV + O media
Keywords: Dispositivo microfluídico; Fertilização in vitro; Polidimetilsiloxano; Teste de termoresistência; In vitro fertilization; Microfluidive device; Polydimethylsiloxane; Thermoresistance test; CIENCIAS AGRARIAS::MEDICINA VETERINARIA